50.27.2 problem 2(c)

Internal problem ID [8183]
Book : Differential Equations: Theory, Technique, and Practice by George Simmons, Steven Krantz. McGraw-Hill NY. 2007. 1st Edition.
Section : Chapter 10. Systems of First-Order Equations. Section 10.2 Linear Systems. Page 380
Problem number : 2(c)
Date solved : Monday, January 27, 2025 at 03:45:30 PM
CAS classification : system_of_ODEs

\begin{align*} x^{\prime }\left (t \right )&=x \left (t \right )+3 y \left (t \right )\\ y^{\prime }\left (t \right )&=3 x \left (t \right )+y \left (t \right ) \end{align*}

With initial conditions

\begin{align*} x \left (0\right ) = 5\\ y \left (0\right ) = 1 \end{align*}

Solution by Maple

Time used: 0.014 (sec). Leaf size: 33

dsolve([diff(x(t),t) = x(t)+3*y(t), diff(y(t),t) = 3*x(t)+y(t), x(0) = 5, y(0) = 1], singsol=all)
 
\begin{align*} x \left (t \right ) &= 2 \,{\mathrm e}^{-2 t}+3 \,{\mathrm e}^{4 t} \\ y &= -2 \,{\mathrm e}^{-2 t}+3 \,{\mathrm e}^{4 t} \\ \end{align*}

Solution by Mathematica

Time used: 0.004 (sec). Leaf size: 38

DSolve[{D[x[t],t]==x[t]+3*y[t],D[y[t],t]==3*x[t]+y[t]},{x[0]==5,y[0]==1},{x[t],y[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} x(t)\to e^{-2 t} \left (3 e^{6 t}+2\right ) \\ y(t)\to e^{-2 t} \left (3 e^{6 t}-2\right ) \\ \end{align*}